Beberapa Faktor yang Berperan Terhadap Keaktifan Kunjungan Lansia ke Posyandu Studi Kasus di Desa Tamantirto Kecamatan Kasihan Kabupaten Bantul Propinsi DIY - Puji Lestari; Soeharyo Hadisaputro; Kris Pranarka (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTFactors influencing elderly visit to elderly community health care (posyandu lansia): Case study in Tamantirto Village, Kasihan, Bantul, DIYBackground: Elderly community health care (ECHC) is the base of holistic-continuous care for the elderly. The number of elderly at Tamantirto Village is 11.3% of the total residents, which has not been accompanied by a high scope of ECHC visit, where 6 of 9 the ECHCs still have the coverage lower than 50%. Purpose of this study is to prove that age, education, occupation, socio economic status, knowledge, attitude, facilities, access, cadre and health workers services, social role and family role can affect elderly people’s visitations to the ECHC.Methods: Study design: observational analytic, case-control approach. The case: elderly as the ECHC members who actively visited, the control: elderly as ECHC members were who did not actively visit ECHC. The sample’s are 52 cases and 52 controls. The quantitative data were gathered by interviews, while the qualitative data by using focus group disscussion.Results: The factors influencing elderly people’s visitations to the ECHC are age of  71 years old (OR:4.6), not working (OR:8.1), good attitude (OR:3), good facilities (OR:5.4), good service of cadres and health workers (OR:6.5) and a good family role (OR:3.2). The factors that do not affect elderly people’s visitations are educational level, socio economic, knowledge, access, and social role ofthe elderly.Conclusion: Characteristics of elderly activity visit ECHC are age of 71 years old, not working, good attitude, good facilities, good service of cadres and health workers and a good family role.Keywords: Elderly community health care, actively visit, influencing factorsABSTRAKLatar belakang: Posyandu lansia merupakan dasar pelayanan yang holistik dan berkesinambungan pada lansia. Jumlah lansia yang cukup banyak di Desa Tamantirto yaitu sebanyak 11,3% dari jumlah penduduk, belum diiringi dengan cakupan kunjungan yang tinggi, dimana 6 dari 9 posyandu masih mempunyai cakupan di bawah 50%. Tujuan penelitian adalah membuktikan bahwa umur, pendidikan, pekerjaan, kondisi sosial ekonomi, pengetahuan, sikap, fasilitas posyandu, akses terhadap posyandu, pelayanan kader dan petugas kesehatan, peran sosial lansia, serta peran keluarga berpengaruh terhadap kunjungan lansia ke posyandu.Metode: Desain penelitian: analitik observasional, pendekatan kasus kontrol. Kasus adalah lansia anggota posyandu (umur 60 tahun) yang aktif melakukan kunjungan ke posyandu. Kontrol adalah lansia anggota posyandu (umur 60 tahun) yang tidak aktifmelakukan kunjungan ke posyandu. Sampel penelitian 52 kasus dan 52 kontrol. Data kuantitatif diperoleh dengan wawancara, data kualitatif dengan diskusi kelompok terarah.Hasil: Faktor yang berpengaruh terhadap keaktifan kunjungan lansia ke posyandu yaitu umur 71 tahun (OR:4,6), tidak bekerja (OR:8,1), sikap yang baik (OR:3), fasilitas yang baik (OR:5,4), pelayanan kader dan petugas kesehatan yang baik (OR:6,5), peran